Redescription and new records of Polymorphus trochus (Van Cleave, 1945) (Polymorphida: Polymorphidae), in Mexico - Caballero-Viñas, Carmen; Sánchez-Nava, Petra; Salgado-Maldonado, Guillermo (Zootaxa, 2019)
Polymorphus trochus Van Cleave, 1945, is an acanthocephalan with limited distribution to the Americas and a common parasite of birds of the Rallidae family (Kinsella et al. 1973, McDonald 1988 and Amin 1992), mainly of the American coot Fulica americana Gmelin, 1789; however, despite existing records of this species, the knowledge and descriptions of its morphological characteristics are not sufficient. Therefore, the identification of this species can be confusing, particularly because it depends on the form of the proboscis of the female. Van Cleave (1945) provided a description and illustrations of this species based on 14 females and 2 males specimens collected in the intestine of F. americana from Lake Buckeye in Ohio, Lake Oneida in New York, and the Illinois River in Illinois; however, this description does not mention many traits that are taxonomically important. Years later, Nickol (1966, thesis not published) provided a description of P. trochus based on 36 mature specimens (14 females and 22 male) from Louisiana, but the author illustrated only the proboscis and included a schematic of the female. He described the shape and size of the proboscis in both sexes, provided measurements of the apical, middle and basal hooks of the proboscis armor, and measurements of the eggs. However, he did not mention the exact distribution of the hooks and spines of the trunk, the measurement of a complete row of hooks nor the shape of all the sexual organs, especially the female ones, which are important taxonomic characteristics in the polymorphids.